2016
DOI: 10.1177/1362361316677838
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of parent-mediated interventions for young children with autism spectrum disorder

Abstract: A number of studies of parent-mediated interventions in autism spectrum disorder have been published in the last 15 years. We reviewed 19 randomized clinical trials of parent-mediated interventions for children with autism spectrum disorder between the ages of 1 and 6 years and conducted a meta-analysis on their efficacy. Meta-analysis outcomes were autism spectrum disorder symptom severity, socialization, communication-language, and cognition. Quality of evidence was rated as moderate for autism spectrum diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
152
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(194 citation statements)
references
References 54 publications
19
152
4
2
Order By: Relevance
“…There was also great disparity in the ‘dose’ of intervention, ranging from a total of 6 hours of intervention (Lawton & Kasari, ) to 40 hours per week for 4 years (Sallows & Graupner, ). Despite this significant heterogeneity, other reviewers have successfully conducted meta‐analyses, for example, with parent‐mediated interventions with similar outcome measures (Nevill et al., ; Oono et al., ) or controlled clinical trials assessing early intensive behavioural interventions (Reichow et al., ). Future reviews may use this strategy to analyse subgroupings of the research studies identified in this review, such as the evidence base for JASPER, and produce additional, meaningful comparisons of the RCT literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also great disparity in the ‘dose’ of intervention, ranging from a total of 6 hours of intervention (Lawton & Kasari, ) to 40 hours per week for 4 years (Sallows & Graupner, ). Despite this significant heterogeneity, other reviewers have successfully conducted meta‐analyses, for example, with parent‐mediated interventions with similar outcome measures (Nevill et al., ; Oono et al., ) or controlled clinical trials assessing early intensive behavioural interventions (Reichow et al., ). Future reviews may use this strategy to analyse subgroupings of the research studies identified in this review, such as the evidence base for JASPER, and produce additional, meaningful comparisons of the RCT literature.…”
Section: Discussionmentioning
confidence: 99%
“…Existing reviews of early treatment for ASD have focused exclusively on specific treatment models such as Applied Behavioural Analysis (Virués‐Ortega, ) or the Early Start Denver Model (Ryberg, ; Waddington, van der Meer, & Sigafoos, ), on treatment approaches more broadly, e.g. behavioural interventions (Reichow, Barton, Boyd, & Hume, ; Warren et al., ), or on a particular mode of delivery such as parent‐mediated interventions (Nevill, Lecavalier, & Stratis, ; Oono, Honey, & McConachie, ). These reviews have varied in the age range included, from under 3 to 4 years to up to 12 years of age with most focusing on children younger than 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…Current best practices in treatment of ASD in young children involve an integration of developmental and behavioral approaches, and inclusion of caregivers in their child's treatment [National Research Council, 2001;Zwaigenbaum et al, 2015]. Several evidence-based interventions have been developed for or adapted to caregiver-mediated models, in which caregivers are trained to provide intervention to their children during play and daily activities (reviewed in Nevill, Lecavalier, & Stratis, 2018;Oono, Honey, & McConachie, 2013). This shift toward more naturalistic treatments and increases in caregiver involvement reflect the importance of teaching skills in a way that generalizes across people and contexts [Schreibman et al, 2015;Vismara & Rogers, 2010].…”
mentioning
confidence: 99%
“…Similarly positive outcomes were reported in the single-case-design literature (Patterson et al, 2012). An updated systematic review and meta-analysis including 19 RCTs published until 2015 shows improved quality of evidence (mostly moderate) and benefit of parent-mediated intervention in reducing children's autism characteristics (Hedges' g=0·22), improving language-communication (g=0·16) and cognition (g=0·24), but with very low quality of evidence supporting improvement in socialization (g=0·22), with no change in outcome with differences in dosage; most studies are however under-powered (Nevill et al, 2016).…”
Section: Parent-mediated Early Interventionmentioning
confidence: 99%